2019
DOI: 10.1002/cpt.1562
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hyponatremia Is Often Drug Induced: 10‐Year Results of a Prospective Pharmacovigilance Program

Abstract: We conducted a prospective evaluation of drug-induced severe hyponatremia (adverse drug reaction (ADR)) through the Prospective Pharmacovigilance Program from Laboratory Signals at Hospital over a period of 10 years. Cases of serum sodium (Na(s)) < 116 mM were recorded from July 2007 to June 2017 (first period). Also cases of Na(s) 116-122 mM were recorded from July 2012 to June 2017 (second period). Drugs were the primary cause of severe hyponatremia. The incidence rate of Na(s) < 116 mM by drugs was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 47 publications
(48 reference statements)
1
25
0
Order By: Relevance
“…The authors acknowledged that PPIinduced hyponatremia is infrequently reported and that their results possibly reflect the high prevalence of PPI prescribing in older hospitalized patients [9]. In other studies, PPI-induced hyponatremia has been reported as a rare cause of drug-induced hyponatremia [6,10]. Unfortunately, we cannot exclude pseudohyponatremia in this case completely.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The authors acknowledged that PPIinduced hyponatremia is infrequently reported and that their results possibly reflect the high prevalence of PPI prescribing in older hospitalized patients [9]. In other studies, PPI-induced hyponatremia has been reported as a rare cause of drug-induced hyponatremia [6,10]. Unfortunately, we cannot exclude pseudohyponatremia in this case completely.…”
Section: Discussionmentioning
confidence: 65%
“…Hyponatremia can often be attributed to medication use [6]. In particular, diuretics (thiazide and thiazide-like drugs) and nervous system drugs (antidepressants, antipsychotic agents, and antiepileptic agents) are known to cause hyponatremia [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,12,13 Thrombocytopenia, anemia, leukocytes in cerebrospinal fluid, pancreatitis, acute kidney injury, and hyponatremia are increasingly frequent druginduced reactions. 14,15,16,17,18,19 This study enabled us to detect a relevant number of ALSs that are potentially related to SADRs and to determine their in-hospital incidence. During March-April 2020, there was a significant 72% reduction in the number of spontaneous SADRs (not from the PPLSH) compared with the same period in 2019, although 4 drug reactions with eosinophilia and systemic symptoms, 2 cases of Stevens Johnson syndrome, and 1 case of acute generalized exanthematous pustulosis were included.…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia is the most common electrolyte disorder among hospitalized patients, particularly among the elderly and women, and in the presence of comorbidities [1][2][3][4][5][6]. Its prevalence varies from 8% to 51%, and it often occurs as an acute disease complication, as a chronic disease decompensation, or as a consequence of interventions during patient treatment [1,5,6]. Hyponatremia is a predictor of poor prognosis in various diseases, including heart failure, coronary syndrome, liver cirrhosis, chronic kidney disease, and stroke [3,5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%